Tracing 33P-labelled organic phosphorus compounds in two soils: New insights into decomposition dynamics and direct use by microbes - Wasner, Daniel; Prommer, Judith; Zezula, David; Mooshammer, Maria; Hu, Yuntao; Wanek, Wolfgang (Frontiers in Soil Science, 2023)
Organic phosphorus (Po) compounds constitute an important pool in soil P cycling, but their decomposition dynamics are poorly understood. Further, it has never been directly tested whether low-molecular weight Po compounds are taken up by soil microbes in an intact form, which reduces the dependence of their P acquisition on extracellular phosphatases. We investigated the short-term fate (24 h) of ﬁve 33P-labelled Po compounds (teichoic acids, phospholipids, DNA, RNA and soluble organophosphates) in two soils. We found indications that soil microbial breakdown of phosphodiesters was limited by the depolymerization step, and that direct microbial uptake of Po occurred to a substantial extent. We postulate a trade-off between direct Po uptake and complete extracellular Po mineralization. These findings have profound consequences for our understanding of microbial P cycling in soils.